The Role of Sustainability Accounting in Enhancing Corporate Reputation A Field Study on Insurance Company Branches in Sirte (Economic studies journal, 2025)
This study aims to explore the role of sustainability accounting in enhancing the reputation of insurance company branches in Sirte, Libya. The study employed a descriptive-analytical approach, utilizing a questionnaire as the data collection instrument (40 questionnaires) administered to the target study sample (managers and employees). Descriptive statistical methods, specifically means and standard deviations, were used to illustrate the opinions of the study sample regarding the study's dimensions. Additionally, inferential statistical methods, namely regression analysis, were employed to test the study's hypotheses.The study concluded that there is a strong positive relationship between sustainability accounting practices (environmental, social, and governance [ESG] disclosure, and integrated reporting) and corporate reputation. Corporate governance disclosure exhibited the most significant impact, followed by environmental disclosure.The study offers practical value to the Libyan insurance sector, recommending that insurance companies adopt sustainability accounting practices, enhance disclosure, strengthen governance, and embrace integrated reporting. The adoption of these practices not only bolsters reputation but also contributes to the achievement of sustainability and corporate social responsibility.
Keywords: Sustainability Accounting; Corporate Reputation; Insurance Companies; Environmental Disclosure; Social Disclosure; Corporate Governance; Integrated Reporting; Libya; Sirte